SARS-CoV-2 Positivity in Asymptomatic-Screened Dental Patients. (June 2021) - Conway, D.I.; Culshaw, S.; Edwards, M.; Clark, C.; Watling, C.; Robertson, C.; Braid, R.; O'Keefe, E.; McGoldrick, N.; Burns, J.; Provan, S.; VanSteenhouse, H.; et al.
Enhanced community surveillance is a key pillar of the public health response to coronavirus disease 2019 (COVID-19). Asymptomatic carriage of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a potentially significant source of transmission, yet remains relatively poorly understood. Disruption of dental services continues with significantly reduced capacity. Ongoing precautions include preappointment and/or at appointment COVID-19 symptom screening and use of enhanced personal protective equipment (PPE). This study aimed to investigate SARS-CoV-2 infection in dental patients to inform community surveillance and improve understanding of risks in the dental setting. Thirty-one dental care centers across Scotland invited asymptomatic-screened patients aged over 5 y to participate. Following verbal consent and completion of sociodemographic and symptom history questionnaire, trained dental teams took a combined oropharyngeal and nasal swab sample using standardized Viral Transport Medium–containing test kits. Samples were processed by the Lighthouse Lab and patients informed of their results by SMS/email with appropriate self-isolation guidance in the event of a positive test. All positive cases were successfully followed up by the national contact tracing program. Over a 13-wk period (from August 3, 2020, to October 31, 2020), 4, 032 patients, largely representative of the population, were tested. Of these, 22 (0.5%; 95% CI, 0.5%–0.8%) tested positive for SARS-CoV-2. The positivity rate increased over the period, commensurate with uptick in community prevalence identified across all national testing monitoring data streams. To our knowledge, this is the first report of a COVID-19 testing survey in asymptomatic-screened patients presenting in a dental setting. The positivity rate in this patient group reflects the underlying prevalence in community at the time. These data are a salient reminder, particularly when community infection levels are rising, of the importance of appropriate ongoing infection prevention control and PPE vigilance, which is relevant as health care team fatigue increases as the pandemic continues. Dental settings are a valuable location for public health surveillance.